The Interest Rate Pass-Through in the Euro Area During the Global Financial Crisis - Timo Wollmershäuser; Nikolay Hristov; Oliver Hülsewig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper uses panel vector autoregressive models and simulations of an estimated DSGE model to explore the reaction of Euro area banks to the global financial crisis. We focus on their interest rate setting behavior in response to standard macroeconomic shocks. Our main empirical finding is that the pass through from changes in the money market rate to retail bank rates became significantly less complete during the crisis. Model simulations show that this result can be well explained by a significant increase in the frictions that the banks business is subject to.
Keywords: E40; E43; E52; 330